2017
DOI: 10.1017/s0954579417000669
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying respiratory sinus arrhythmia: Effects of misspecifying breathing frequencies across development

Abstract: Low resting respiratory sinus arrhythmia (RSA), and to a lesser extent excessive RSA reactivity to emotion evocation, are observed in many psychiatric disorders characterized by emotion dysregulation, including syndromes spanning the internalizing and externalizing spectra, and other conditions such as nonsuicidal self-injury. Nevertheless, some inconsistencies exist. For example, null outcomes in studies of RSA-emotion dysregulation relations are sometimes observed among younger participants. Such findings ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(161 citation statements)
references
References 132 publications
(241 reference statements)
4
155
2
Order By: Relevance
“…For example, Crowell et al () found minute‐to‐minute concordance between observed aversiveness and physiological dysregulation among a sample of depressed and self‐injuring adolescents. Mothers and teens demonstrated RSA withdrawal to their own and their dyad partner's aversive behavior, indicating poor physiological regulation in response to conflict (Shader et al, ). In contrast, control dyads showed RSA increases during aversive displays.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Crowell et al () found minute‐to‐minute concordance between observed aversiveness and physiological dysregulation among a sample of depressed and self‐injuring adolescents. Mothers and teens demonstrated RSA withdrawal to their own and their dyad partner's aversive behavior, indicating poor physiological regulation in response to conflict (Shader et al, ). In contrast, control dyads showed RSA increases during aversive displays.…”
Section: Introductionmentioning
confidence: 99%
“…Second, various studies have not corrected for respiratory parameters in quantifying RSA. Thus, consistent with the recommendations of Shader et al (2018), the current study used different respiration bands to calculate RSA for different age groups and compared to previous common practice of using the typical and the same respiration band. Third, researchers recently have pointed out that previous studies have mis-specified breathing frequencies and age-corrected frequency bands should be used to quantify RSA (Shader et al, 2018).…”
Section: Methodological and Analytical Limitationsmentioning
confidence: 87%
“…First, when assessing RSA reactivity, previous studies have used standardized residual scores (e.g., El-Sheikh et al, 2009;Obradović et al, 2010), which are between-subject rather than within-subject changes, although they are closely linked to simple change scores which better reflect RSA reactivity. Third, researchers recently have pointed out that previous studies have mis-specified breathing frequencies and age-corrected frequency bands should be used to quantify RSA (Shader et al, 2018). RSA values are typically confounded with concurrent physical activity which may alter respiration (Grossman & Taylor, 2007;Overbeek, van Boxtel, & Westerink, 2012).…”
Section: Methodological and Analytical Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as noted by Shader et al (2018), this range includes adult respiratory frequencies (i.e., those falling below 0.28 Hz), which may have introduced noise into our RSA calculations and underestimated children's parasympathetic reactivity patterns. Importantly, Shader et al (2018) focused on parasympathetic withdrawal, rather than augmentation; thus, it is not clear whether and how respiratory frequency bands may influence estimates of parasympathetic augmentation. Importantly, Shader et al (2018) focused on parasympathetic withdrawal, rather than augmentation; thus, it is not clear whether and how respiratory frequency bands may influence estimates of parasympathetic augmentation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%